Optimasi Proses Dealuminasi Modernite sebagai Katalis Perengkahan Minyak Goreng Bekas menjadi Biofuel - Didi Dwi Anggoro; Luqman B; Setia Budi S; Nita A; Rohmadona H; Sigit B (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
Used cooking oil is a food industry waste and household waste, which has high potential to be used as biofuel feedstock, which has the chain of carbon and hydrogen atoms high. Biofuel can be produced by the method of catalytic cracking. Modernite is potential to be used as an acid catalyst for the cracking process. To get a good acidity catalyst, modernite can be modified catalyst by dealumination process. The raw material used is used cooking oil and used modernite type zeolite catalyst with a trademark CBV 21A, which having a mole ratio of SiO2 / Al2O3 of 20 and a surface area of 500 m2/g. The reactor used in the form of a catalytic reactor and a three-stage process i.e dealumination of the catalyst, catalyst calcination process, and catalyst testing to reaction of used cooking oil catalytic cracking. Dealuminated catalyst is carried on a temperature that is 30, 50, 70°C. Modernite catalyst dealumination results included in the pipe nozzle and injected into the furnace by flowing N2 gas at a temperature of 600oC for 5 jam. For catalyst testing for used cooking oil cracking reaction under temperature 450 oC. In this study, the optimization equation for the liquid product is Y = 2,801712 + 0,296807 X1 + 0,579137 X2 + 0,486784 X3 – 0,1875 X - 0,2125 X2X3 – 0,211775 X1^2 + 0,467905 X2^2 – 0,59326 X3^2